‘This year I will not put her to work’: the production/reproduction nexus in Burkina Faso - Storeng, Katerini Tagmatarchi (Taylor & Francis, 2012)
Global advocacy campaigns increasingly highlight the negative impact of reproductive morbidity on economic productivity and development in order to justify donor investment in maternal health. Anthropological approaches nuance such narrow economic estimations of reproductive health. Drawing on ethnographic fieldwork from Burkina Faso in West Africa, this paper analyses the dynamic, and sometimes contradictory, relationship between women's work and reproductive health in impoverished communities. Specifically, it examines the consequences of life-threatening ‘near-miss’ obstetric complications for women's work across domestic, agricultural and economic spheres over a four-year period. Such events provide a window onto the diverse ways in which production and reproduction are intimately linked within women's everyday lives. Reproduction and production entail sources of potential empowerment and enhancement, as well as potential threats, to health and well-being. In the aftermath of ‘near-miss’ events, the realms of reproduction and production sometimes jeopardise each other and at other times reinforce each other, while strength in one domain can compensate for weakness in the other. Women's experiences thus reveal how ‘production’ and ‘reproduction’ are mutually constituted, challenging the purely instrumental accounts of pregnancy-related ‘productivity loss’ that dominate current global health discourse.